The Influence of Camel Analysis, SBI Rate and Exchange Rate toward Stock Return on Banking Industries listed in Indonesian Stock Exchange period 2009-2013 - admin, Laras Nindya Malini B12112010 (Jurnal Manajemen Update, 2016)
This research aimed to examine the influence of CAMEL analysis, Exchange Rate and SBI Rate towards Stock Return on banking companies listed in Indonesian Stock Exchange during 2009-2013. Banking sector is one of the fastest growing sectors in Indonesia. Nowdays, banking sector become more complex. In addition, evaluating banking sectors is not easy, there are so many factors which need to taken care while evaluating good banks from bad ones. In order to evaluate the influence between the internal and externals factros influencing banksâ€™ stock return this research choosen CAMEL models. The population in this research are the companies that are continously listed on the Indonesian Stock Exchange for five consecutive years starting from 2009-2013. The sampling method used in this research is purposive sampling which make up for a sample of 17 companies. Panel data is employed to test the variables to investigate with the total account of observation 85 observation. Generalized Least Square is utilized to test the data and the result shows that the internal factors such as Capital Adequacy Ratio (CAR), Non-Performing Loan (NPL) and Return on Asset (ROA) have positive influence towards Stock Return. The exchange rate fluctuations has negative sign towards stock return while SBI rate has positive influence upon the Stock Return. Â  Keywords: Stock Return, CAMEL, SBI Rate and Exchange Rates.